Differential Methylation in Promoter Regions of the Genes NR3C1 and HSP90AA1, Involved in the Regulation, and Bioavailability of Cortisol in Leukocytes of Women With Preeclampsia - Torres-Salazar, Quitzia; Martínez-López, Yolanda; Reyes-Romero, Miguel; Pérez-Morales, Rebeca; Sifuentes-Álvarez, Antonio; Salvador-Moysén, Jaime (Frontiers in Medicine, 2020)
Introduction: Hypertensive disorders are of interest in obstetrics and gynecology because they are the second place among causes of maternal mortality, and a source of complications in the short, mid, and long term. Even if pathophysiological process behind preeclampsia (PE) is still unknown, stress factors have been revealed to play an important role in the genesis of this pathologic process. Methods: A case-control study was designed with the purpose of determining if there is a differential methylation in NR3C1, HSD11B2, CYP11A1, CRHBP, TEAD3 and HSP90AA1 genes, related with signaling of the hypothalamic-pituitary-adrenal axis, and its regulation on early-onset preeclampsia (EOPE). Results: A total of 20 cases and 20 controls were studied by DNA methylation analysis, demonstrating differences amongst groups in the percentage of methylation of NR3C1 gene. After a contingency analysis, an OR for preeclampsia of 12.25 was identified for NR3C1 and 9.9 for HSP90AA1 genes. NR3C1, TEAD3 and HSP90AA1 genes showed a positive correlation with the systolic and diastolic blood pressure levels with a p ≤ 0.05. Conclusion: This study found a differential methylation in the glucocorticoid receptor (GR) NR3C1 and its co-chaperone HSP90AA1 in women with PE, with a possible regulatory role in the response to stress in pregnancy and is a likely physiopathological mechanism in PE.